Pathological features of hypertrophic cardiomyopathy without asymmetrical septal hypertrophy. Issue 3 (September 1986) - Tanaka, M; Fujiwara, H; Kawai, C
Abstract : In a heart with hypertrophic cardiomyopathy without asymmetrical septal hypertrophy the number of transmural myocytes, the mean size of myocytes, and the percentage area of interstitial space were similar in the ventricular septum and left ventricular posterior wall, whereas in a reported series of 14 hearts with hypertrophic cardiomyopathy with asymmetrical septal hypertrophy the number of transmural myocytes was greater in the ventricular septum than in the left ventricular posterior wall. In hearts with hypertrophic cardiomyopathy without asymmetrical septal hypertrophy the mean size of myocytes was significantly greater than that of normal hearts, but the number of transmural myocytes was not increased. The extent and distribution pattern of myocardial fibre disarray and fibrosis in the left ventricle were similar in hearts with hypertrophic myopathy whether or not asymmetrical septal hypertrophy was present.